Mitochondrial evolution in the entomopathogenic fungal genus Beauveria. Issue 4 (30th October 2020) - Glare, Travis; Campbell, Matt; Biggs, Patrick; Winter, David; Durrant, Abigail; McKinnon, Aimee; Cox, Murray
Abstract: Species in the fungal genus Beauveria are pathogens of invertebrates and have been commonly used as the active agent in biopesticides. After many decades with few species described, recent molecular approaches to classification have led to over 25 species now delimited. Little attention has been given to the mitochondrial genomes of Beauveria but better understanding may led to insights into the nature of species and evolution in this important genus. In this study, we sequenced the mitochondrial genomes of four new strains belonging to Beauveria bassiana, Beauveria caledonica and Beauveria malawiensis, and compared them to existing mitochondrial sequences of related fungi. The mitochondrial genomes of Beauveria ranged widely from 28, 806 to 44, 135 base pairs, with intron insertions accounting for most size variation and up to 39% ( B. malawiensis ) of the mitochondrial length due to introns in genes. Gene order of the common mitochondrial genes did not vary among the Beauveria sequences, but variation was observed in the number of transfer ribonucleic acid genes. Although phylogenetic analysis using whole mitochondrial genomes showed, unsurprisingly, that B. bassiana isolates were the most closely related to each other, mitochondrial codon usage suggested that some B. bassiana isolates were more similar to B. malawiensis and B. caledonica than the other B. bassiana isolates analyzed. Graphical abstract: Mitochondrial composition and order of Beauveria bassiana Bb147 (GenBank Accession EU100742). Circular mitochondrial genome of 32, 263 base pairs from Beauveria bassiana Bb147 is depicted as linear. Features are color‐coded to corresponding complexes or function as depicted in the legend. Complex 1 (NADH dehydrogenase)—yellow, complex III (ubichinol cytochrome c reductase)—light green, complex IV (cytochrome c oxidase)—fuschia, ATP synthase—green, ribosomal proteins—brown, transfer RNAs—blue, ribosomal RNAs—red and introns—white. All features are encoded on the +strand. Research Highlights: We compared the mitochondrial sequences of Beauveria and related genera. Gene arrangement was conserved between the Beauveria, but codon usage and genome length varied. Introns were the main source of diversity, including length.